HUBUNGAN POWER OTOT LENGAN DAN BAHU TERHADAP HASIL LEMPAR LEMBING PADA ATLET PUTRA PPLP RIAU - Sari, Maulida; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is less away shots from the target has been determined, the lack of a muscle in the towel when the spear is removed from the hands, slow it started the movement at arm elbow pitcher is strengthened so that a less than the maximum. The aim in this research is to find out if there is a power arm muscles and shoulders to the result thrown the spear, on the athletes son PPLP Riau. The population in this research are all athletes son PPLP Riau which amounted to 7 people. The sampling of the whole population (the total sampling). Instrument is used in this research is a test of Medicine Ballthrow and javelin throw. The data obtained were analysed using techniques korelasi product moment. Based on the result of research and data processing in the statistics research, it can be concluded that for the correlation between variable (x) with variable (y) and by the value of r = 0,976 the rxy > rtabel the (0,976 > 0,811), then Ha reveived, in other words there is a significant connection between power arm muscles and shoulders to the result thrown the spear, on the athletes son PPLP Riau.Keywords : Power the shoulder, the result thrown spear